If f(x) = -2x + 7 and g(x) = x^2 – 2, what is (f•g)(3)?

Question

If f(x) = -2x + 7 and g(x) = x^2 – 2, what is (f•g)(3)?

in progress 0
Claire 1 month 2021-10-15T22:18:59+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-15T22:20:00+00:00

    Answer:

    = 7

    Step-by-step explanation:

    If f(x) = -2x + 7 and g(x) = x^2 – 2, what is (f•g)(3)?

    (f. g) = (-2x + 7)(x² – 2)

    = -2x (x² – 2) +7( x² -2)

    =-2x³ + 4x + 7x² – 14

    (f. g) (3) means when x = 3

    = -2x³ +4x + 7x² – 14

    = -2(3)³ + 4(3) + 7(3)² – 14

    = -2(27) +12 +7(9) – 14

    = -54 +12+63-14

    =75 – 68

    = 7

    I hope this was helpful, please mark as brainliest

    0
    2021-10-15T22:20:07+00:00

    Answer:

    (f•g)(3) = -7

    Step-by-step explanation:

    f(x)=-2x + 7

    g(x) = x^2 – 2

    (f•g)(3) = -2(x² – 2) + 7

    (f•g)(3) = -2x² + 4 +7

    (f•g)(3) = -2x² + 11

    (f•g)(3) = -2(3)² + 11

    (f•g)(3) = -2(9) + 11

    (f•g)(3) = -18 + 11

    (f•g)(3) = -7

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )